Brain activity during acquisition of long visuospatial sequences - Mihovilovic, Milena I.; Stephan, Thomas; Straube, Andreas; Dieterich, Marianne; Eggert, Thomas (Frontiers in Cognition, 2025)
Explicitly acquiring a visuospatial sequence involves various fundamental attentional and processing mechanisms that can be difficult to disentangle. To this end, we performed an fMRI study (n = 34) on the acquisition of visuospatial targets in a delayed imitation paradigm. Task phases alternated between presentation and recall of a 20-target-long sequence. Behavioral data from the recall phase was used to determine encoding progress as a function of time during presentation, with this progress taken as a continuous predictor of BOLD activity. A separate, attention-only task was devised in order to isolate activity related to spatial attention shifts specifically. General linear model analysis using the constructed learning and attention predictors revealed heightened activation for both tasks in bilateral superior parietal lobules (SPL), bilateral V5, and bilateral middle frontal gyri (MFG). Increased response during learning was seen in the SPL and V5, but not MFG. Repeated measures ANOVA indicated significant interactions between region and task, as well as a right-biased tendency in the hemisphere*task interaction. This suggests a role for the SPL and V5 during sequence acquisition that cannot be explained by attention alone.